Edukasi Siap Hadapi Pandemi Covid-19 dengan Gizi Seimbang - Oktaviasari, Dianti Ias; Purnamasari, Vivien Dwi (Institut Ilmu Kesehatah Bhakti Wiyata Kediri, 2021)
Coronavirus Disease 2019 (COVID-19) is a new type of disease that has never been previously identified in humans, is a respiratory disease that is contagious and can lead to death. Educating the public in breaking the chain of spread of the Covid-19 virus is not only an appeal to comply with protocols in breaking the chain of virus spread, but the community also needs to get education on the importance of increasing endurance, especially with the principle of balanced nutrition. Seeing the incidence of Covid-19 which is still increasing, and the importance of the community to be aware and willing to apply the principle of balanced nutrition to maintain body immunity, it is necessary to have good education and knowledge from the community in order to provide good nutritional needs in the family. The purpose of this community service activity is to increase the target group's knowledge of balanced nutrition during the Covid-19 pandemic, so that it is hoped that the target group will know and want to apply the principle of balanced nutrition so that it can increase immunity and prevent infection with the Covid-19 virus. The method of implementing community service is the method of providing education with counseling to community leaders and media posters about balanced nutrition in communities in isolation areas in Kelurahan Centong and Singonegaran Kota Kediri. The success of the activity is marked by an indicator of increasing knowledge as measured by the results of the pre-test and post-test. The results of the data analysis showed an increase in the knowledge of the target community to 82%, and the analysis with the Paired Sample T-Test with Î± = 0.05 showed p = 0.000, which is a significant difference between the level of knowledge of mothers under five before and after receiving education. The conclusion of the Community Service activities shows that activities can effectively increase the knowledge of the target community regarding the principle of balanced nutrition to increase body immunity during the Covid-19 pandemic. It is hoped that the follow-up of this activity is an increase in community behavior to implement the principle of balanced nutrition and an increase in the provision of information and assistance to the community by utilizing digital media so that it can reach the wider community.